Effects of a multicomponent exercise regimen on subchondral bone and cartilage in postmenopausal women with knee osteoarthritis: protocol for a randomized controlled trial - Konola, Ville-Markus; Parkkari, Jari; Multanen, Juhani; Nikander, Riku; Rantalainen, Timo; Vesanto, Johanna; Pekkala, Satu; Kalaja, Merja; Ihalainen, Johanna K.; Waller, Benjamin; Munukka, Matti; Sievänen, Harri; et al. (Current controlled trials in cardiovascular medicine, 2025)
Background Knee osteoarthritis (KOA) is considered a whole-joint disease that is amenable to prevention and treatment in the early stages. Exercise is among the core treatment recommendations for KOA and it has been suggested that optimal exercise regimens should improve aerobic capacity and knee extensor strength. Subchondral bone and articular cartilage are functionally paired, and information on the responses of these tissues to exercise may help in the development of efficacious and feasible exercise regimens that can potentially improve bone and cartilage properties. This article describes a clinical trial investigating the effects of a multicomponent exercise regimen on the subchondral bone and articular cartilage of the knee joint in postmenopausal women with mild KOA. Methods A minimum of 90 postmenopausal women between the ages of 55 and 75 meeting the inclusion criteria will be recruited. After an initial assessment, the participants will be randomly assigned to two groups. The intervention group will participate in a progressive multicomponent exercise regimen, including step aerobics and resistance training alternating every 2 weeks, for 50 min three times a week for 8 months. The reference group will be conducting home exercise program representing standard rehabilitative management for KOA patients. The primary outcome measures of this trial are the 8-month changes in the biochemical composition of the knee articular cartilage measured by the T1r and T2 relaxation times from quantitative magnetic resonance imaging and subchondral bone sclerosis, density and structure as measured via cone beam computed tomography. Measurements will be performed at baseline, after the 8-month intervention period, and at 12 months of maintenance. Discussion This RCT investigates the effectiveness of a multicomponent exercise regimen on the subchondral bone and cartilage of the knee joint and the potential interaction between these tissues. The information gained will improve our understanding of the effects of exercise on subchondral bone and the biochemical properties of articular cartilage and improve the prescription of multicomponent exercise regimens in the management of mild KOA. Trial registration ClinicalTrials.gov NCT06173193. Retrospectively registered before completion of the recruitment on 31 October 2023, https://www.clinicaltrials.gov/study/NCT06173193 .